Upaya Peningkatan Kesehatan Lansia Dengan Rematik Di Dusun III Desa Suka Sari Kec. Kebawetan Kab. Kepahiang Melalui Pelaksanaan Senam Rematik - Ramadhani, Aidila Fitri; Sari, Zalpa Entin; Bunga Rizqi, Dwi Putri; Salsa Billah, Nur Azizah; Dona, Yepi Lisma; Rossita, Taufianie (Universitas Dehasen Bengkulu, 2026)
Elderly people with rheumatism often face joint pain, limited mobility, and a decreased quality of life that hinders daily activities. Rheumatic exercise is a non-pharmacological intervention based on structured physical exercise that aims to improve joint fitness, reduce pain, and improve the physical condition of the elderly. This study was conducted in Hamlet 3, Suka Sari Village, Kebawetan District, Kepahiang Regency, as an effort to improve the health of the elderly through regular rheumatic exercise training guided by health cadres and medical personnel. The activity methods included education on the benefits of exercise, movement consolidation, and rheumatic exercise practice over several sessions. The results showed an increase in the elderly's understanding of appropriate physical activity for their condition and a decrease in pain complaints after participating in rheumatic exercise. These findings indicate that rheumatic exercise is an effective promotive strategy for improving the health of elderly people with rheumatism in the community.